The nitrogen isotope composition of sediments from the proto‐North Atlantic during Oceanic Anoxic Event 2. (23rd July 2015) - Ruvalcaba Baroni, I.; van Helmond, N. A. G. M.; Tsandev, I.; Middelburg, J. J.; Slomp, C. P.
Abstract Sediment records of the stable isotopic composition of N (δ15N) show light δ15N values at several sites in the proto‐North Atlantic during Oceanic Anoxic Event 2 (OAE 2) at the Cenomanian‐Turonian transition (∼94 Ma). The low δ15N during the event is generally attributed to an increase in N2 fixation and incomplete uptake of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2f6znvj6" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />4+</alternatives> for phytoplankton growth. A compilation of all reliable data for the proto‐North Atlantic during OAE 2 demonstrates that the most pronounced negative shift in δ15N from pre‐OAE 2 to OAE 2 occurs in the open ocean but with δ15N never lower than −3‰. Using a box model of N cycling for the proto‐North Atlantic during OAE 2, we show that N2 fixation is a major contributor to the δ15N signal, especially in the open ocean. Incomplete uptake of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2f6znvm9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />4+</alternatives> for phytoplankton growth is important in regions dominated by downwelling, with lateral transport of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2f6znvkr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />4+</alternatives> acting as a major source. In the southern proto‐North Atlantic, where bottom waters were euxinic, the light δ15N signature is largely explained by upwelling of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2f6znvbw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />4+</alternatives>. Our study provides an overview of regional differences in δ15N in the proto‐North Atlantic and highlights the role of lateral exchange of water and nutrients, in addition to local biogeochemical processes, in determining δ15N values of OAE 2 sediments.